Ethnomedicinal Plant Resources of Tamang Community in the Konjyosom Rural Municipility, Central Nepal - Silwal Gautam, Ratna; Shrestha, Sudha Joshi; Shrestha, Ila (Ethnobotany Research and Applications, 2023)
Background: In Nepal, plant resources play an important role in the health of local communities. However, in many parts of the country, this role and its patterns are understudied. The purpose of this study was to document medicinal plant species and assess their use among the Tamang community in Lalitpur district, Central Nepal. Methods: Ethnomedicinal information was collected through focus group discussions, semi structured interviews with local peoples and key informants from the Tamang community using rapid rural appraisal tools (RRA) across the five wards vz. Nallu, Chaughare, Bhardew, Dalchoki and Sankhu of the Konjyosom rural municipality. Botanical voucher samples were collected for scientific identification. The quantitative data were analyzed for informants consensus factor (ICF), fidelity level (FL) and relative frequency of citation (RFC). Results: A total of 176 plant species were recorded under 82 families and 158 genera as medicinal to treat different ailments. Among them, 169 species were angiosperms, one gymnosperm and six pteridophytes. Herbs (78 spp.) occurred most frequently in the study area, and the leaves (38 spp.) were commonly foraged. The most common route of consumption was oral (98 spp.) and the paste (36 spp.) was frequently administered. The majority of the species (58%) were collected from the forest. The ICF value ranged from 0.26 (digestive) to 0.97 (respiratory). The RFC value ranged from 0.01 to 0.87. Curcuma longa had the highest frequency of citation index of 0.87. is this RFC? Merge these 2 sentences The FL index ranged from 42.86% to 100%. The most preferred medicinal plant species was Curcuma longa which was used to treat cuts and wounds and common cold (51%). Conclusion: Medicinal plants have played a significant role in the health care of local people. This study provides a comprehensive documentation of ethnomedicinal plant species using among the Tamang community of Konjyosom rural municipality, Lalitpur district. This study concluded that it is necessary to document and preserve biodiversity and its associated knowledge, which may lead to additional research activities. Keywords: Ethnic people; Ethnobotanical, Informants, Interview